PREVENTION OF THE TRANSNATIONAL CRIMINAL IN INDONESIA - Muhammad Arief Hamdi (Polteknik Imigrasi, 2018)
Transnational crime as a form of crime that can threaten the potential of community life such as economic, social, public order and the security of both national and regional. The development of transnational crime in Indonesia, as the impact of globalization as well as other factors relating to the movement of people from one area of the country to country or from an area to another area. So, very potential appears and the development of a new type of cross border crime. The purpose of the research was to discover different shapes or types of crimes that can be categorized as a transnational crime which differentiate it from other crimes; Map the concept of handling and tackling transnational crime for the benefit of Indonesia; Find a harmonization of national laws and international laws related to cross border crime. That to overcome the widespread crime, the necessary legal instrument relating to the types of crime that either national law or international law/international agreements with the protocol. On the other hand, the state was instrumental in anticipation of the influx of threats will be crimes is cross border through negotiations/diplomacy and cooperation-bilateral or multilateral cooperation is good.